Doing secularism: commemorating the national day of laïcité in French schools. Issue 2 (15th March 2022) - Almeida, Dimitri
ABSTRACT: After the terrorist attacks of January 2015, laïcité – the particular French version of secularism – has been at the centre of government efforts to reaffirm republican values and strengthen national cohesion. One of the most emblematic measures in this quest was the decision to have state schools celebrate a national day of laïcité . This article seeks to understand how French secularism has been performed during these commemorations. It draws from the assumption that secularism does not only consist of rules on church-state relations and on how religion may or may not manifest itself in the public sphere, but also of representations and routinised practices of secularity. Through an online analysis of nearly 150 school activities organised between 2015 and 2020 across France, this article shows how laïcité remains an indeterminate construct. Commemorations typically take the form of tree-planting ceremonies, re-enacting rituals, and visual or performing arts projects. In many cases, laïcité is diluted in civil religious rituals to the point that it sometimes becomes an empty signifier of patriotism. Other projects, however, reinterpret laïcité as a condition for multicultural citizenship and, in doing so, propose counter-narratives to the notion that multiple identities pose a threat to the Republic.